2021
DOI: 10.3390/biom11111615
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxidative Stress on Neurological Outcomes in Spontaneous Intracerebral Hemorrhage

Abstract: Spontaneous intracerebral hemorrhage (ICH) causes, besides the primary brain injury, a secondary brain injury (SBI), which is induced, amongst other things, by oxidative stress (OS) and inflammation, determining the patient’s outcome. This study aims to assess the impact of OS in plasma and cerebrospinal fluid (CSF) on clinical outcomes in patients with ICH. A total of 19 ICH (volume > 30 cc) patients and 29 control patients were included. From day one until seven, blood and CSF samples were obtained, and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…The main physiological functions of GSH are scavenging free radicals, anti-oxidation and anti-aging. The present study also found that plasma levels of GSH was decreased significantly in ICH patients from days 1-7, however, this trend was not statistically significant ( 34 ). The results of the present study also showed that GSH levels declined gradually over time in the TBI group; notably, there was no statistically significant comparison between the groups.…”
Section: Discussioncontrasting
confidence: 51%
“…The main physiological functions of GSH are scavenging free radicals, anti-oxidation and anti-aging. The present study also found that plasma levels of GSH was decreased significantly in ICH patients from days 1-7, however, this trend was not statistically significant ( 34 ). The results of the present study also showed that GSH levels declined gradually over time in the TBI group; notably, there was no statistically significant comparison between the groups.…”
Section: Discussioncontrasting
confidence: 51%
“…The intra-assay and inter-assay CVs were 3.1% and 5.1%, respectively; the detection limit was 7 mmol/L. TAC was measured by a colorimetric test system (ImAnOx kit, Immundiagnostik AG, Stubenwald-Allee 8a, and D 64,625 Bensheim, Germany) [ 18 , 19 ], which reflects the sum of all antioxidant components, through an enzymatic reaction of sample antioxidants with a defined amount of exogenously provided H 2 O 2 . The antioxidants in the sample eliminate a certain amount of the provided H 2 O 2 , which involves the conversion of tetramethylbenzidine to a colored product measured at 450nm wavelength.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have studied the impact of OS in plasma and cerebrospinal fluid (CSF) of patients with ICH on their clinical outcomes. The results showed that elevated MDA in CSF and total antioxidant status in plasma were associated with harmful outcomes, while higher plasma SOD and GSH-Px were associated with favorable outcomes in ICH (Masomi-Bornwasser et al, 2021 ). This reflects the predictive power of oxidative markers for ICH outcomes.…”
Section: Clinical Impact Of Oxidative Stress In and Treatment Of Ichmentioning
confidence: 99%